2010
DOI: 10.1007/s00262-010-0837-x
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic alcohol consumption enhances myeloid-derived suppressor cells in B16BL6 melanoma-bearing mice

Abstract: We previously found that chronic alcohol consumption decreases the survival of mice bearing subcutaneous B16BL6 melanoma. The underlying mechanism is still not completely understood. Antitumor T cell immune responses are important to inhibiting tumor progression and extending survival. Therefore, we examined the effects of chronic alcohol consumption on the functionality and regulation of these cells in C57BL/6 mice that chronically consumed 20% (w/v) alcohol and subsequently were inoculated subcutaneously wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 48 publications
3
20
0
Order By: Relevance
“…The present study further supports the concept that chronic alcohol consumption accelerates the dysfunction of the immune system in the melanoma-bearing mice such as skewing iNKT cell cytokine profile from Th1-dominant to Th2 dominant as we reported in the present study, and inhibiting tumor-specific CD8 + T cell expansion and accelerating the decay of IFN-γ-producing CD8 + T cells as previously reported [26]. Although we found that alcohol consumption inhibits tumor growth and that immunization with a melanoma lysate further inhibits the growth of tumor in alcohol-consuming mice (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The present study further supports the concept that chronic alcohol consumption accelerates the dysfunction of the immune system in the melanoma-bearing mice such as skewing iNKT cell cytokine profile from Th1-dominant to Th2 dominant as we reported in the present study, and inhibiting tumor-specific CD8 + T cell expansion and accelerating the decay of IFN-γ-producing CD8 + T cells as previously reported [26]. Although we found that alcohol consumption inhibits tumor growth and that immunization with a melanoma lysate further inhibits the growth of tumor in alcohol-consuming mice (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Immunization could further accelerate and amplify this process. Additional evidence supporting this is our previous finding that alcohol consumption accelerates the dysfunction of CD8 + T cells within two weeks after melanoma inoculation [26]. These functional changes in the immune system are reflected in the lack of a survival benefit in the melanoma-bearing mice.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…These enzymes metabolize arginine to decrease the availability of this amino acid, which in turn (1) block the translation of CD3ζ, one of the important components of TCR complex; (2) inhibit T cell proliferation; and (3) promote T cell apoptosis [ 57 ]. We found that chronic alcohol consumption signifi cantly upregulates the expression of IL-4/IL-13 receptor α-chain (CD124) on MDSC [ 55 ], and decreases the concentration of arginine in the plasma of melanoma-bearing mice [ 35 ]. The increased MDSC could be associated with the inhibition of the memory and tumor-specifi c CD8 + T cell proliferation and dysfunction in the tumor-bearing mice.…”
Section: Effects Of Chronicmentioning
confidence: 94%